Candidate biomarkers of PARP inhibitor sensitivity in ovarian cancer beyond the BRCA genes. Issue 11 (27th November 2018) - Hodgson, Darren; Dougherty, Brian; Lai, Zhongwu; Fielding, Anitra; Grinsted, Lynda; Spencer, Stuart; O'Connor, Mark; Ho, Tony; Robertson, Jane; Lanchbury, Jerry; Timms, Kirsten; Gutin, Alexander; et al.
Abstract Background Olaparib (Lynparza™) is a PARP inhibitor approved for advancedBRCA -mutated (BRCA m) ovarian cancer. PARP inhibitors may benefit patients whose tumours are dysfunctional in DNA repair mechanisms unrelated toBRCA1/2 . We report exploratory analyses, including the long-term outcome of candidate biomarkers of sensitivity to olaparib inBRCA wild-type (BRCA wt) tumours. Methods Tumour samples from an olaparib maintenance monotherapy trial (Study 19, D0810C00019; NCT00753545) were analysed. Analyses included classification of mutations in genes involved in homologous recombination repair (HRR), BRCA1 promoter methylation status, measurement of BRCA1 protein and Myriad HRD score. Results Patients withBRCA m tumours gained most benefit from olaparib; a similar treatment benefit was also observed in 21/95 patients whose tumours wereBRCA wt but had loss-of-function HRR mutations compared to patients with no detectable HRR mutations (58/95). A higher median Myriad MyChoice® HRD score was observed inBRCA m andBRCA wt tumours withBRCA1 methylation. Patients withoutBRCA m tumours derived benefit from olaparib treatment vs placebo although to a lesser extent thanBRCA m patients. Conclusions Ovarian cancer patients with tumours harbouring loss-of-function mutations in HRR genes other thanBRCA1 /2 may constitute a small, molecularly identifiable and clinically relevant population who derive treatment benefit from olaparib similar to patients withBRCA m.